Regulation Studies Of Polyhydroxyalkanoate Synthase Genes In Pseudomonas Sp. USM 4-55 - Tan , Yifen (2010)
Polyhydroxyalkanoate (PHA) is a class of naturally occurring polyesters that serve as intracellular energy storage material for bacteria that facilitates its survival during extreme environmental conditions. The relative quantification of mRNA transcripts of three PHA synthase genes, phaC1, phaC2 and phbC in Pseudomonas sp. USM 4-55 was examined utilizing quantitative reverse transcription-real time PCR (RT-qPCR). The transcript level of phbC was the most abundant followed by phaC1 and then phaC2 when grown on either oleic acid, PFAD or glucose as the sole carbon source during log and stationary phase. The transcript level of phaC1 was found to be ten times higher or more than the transcript level of phaC2. In PFAD culture, the highest recorded PHA production was 50 wt% with 66 mol% of mcl monomers during the late log phase; while glucose produced highest PHA of 30 wt% with 72 mol% of 3HB (scl) monomer during the stationary phase. The RT-qPCR and the reverse transcription PCR (RT-PCR) revealed that phaC1 and phaC2 are not cotranscribed and possess their own promoters while the phbC is transcribed as the phbBAC operon and controlled by a single promoter which is active even during stationary phase. Promoter prediction using BPROM and PromScan disclosed a σD- and a σN-dependent promoter region at 206 bp and 125 bp upstream of phaC1 respectively.